An Assessment on the Structure of Shariah Audit Function: The Case of Malaysian Takaful Industry - Noor Aimi Mohamad Puad; Nurdianawati Irwani Abdullah; Zurina Shafii (Journal of Islamic Finance, 2022)
The Islamic financial system's beneficial expansion has resulted in a rise in the number of products and services offered by Islamic financial institutions (IFIs). However, IFIs may have neglected key factors that could have had an impact on the products and services they provide which is 'Shariah compliance'. This circumstance necessitates a system of internal check-and-balance procedures. As one of the components of Shariah governance, the Shariah auditor is responsible for ensuring the efficacy of the internal control system for Shariah compliance. Prior research reveals that the current framework explains very brief on Shariah audit function, thus lead to the various practices by takaful operators which may affect the effectiveness of the Shariah audit process. The aim of this study is to assess the structure of Shariah audit function practiced by Malaysian takaful operators. To this end, semi-structured interviews were conducted involving selected Shariah auditors for every takaful operators in Malaysia. Reflexive thematic analysis influenced by a constructivist perspective was used to analyse data using a combination of inductive and deductive methodologies. Recognizing the model adapted by takaful operators can help in understanding further the execution of the Shariah audit process. At the same time, the commitment of these takaful operators can be observed in providing one of the Shariah compliance functions as required in the Shariah Governance Framework. The study discovered that none of the takaful operators in Malaysia have specific departments or unit for Shariah audit function. This study may provide relevant guidelines especially for policymaker in developing a more comprehensive framework for Shariah audit, and at the same time is useful for takaful industry in enhancing their Shariah audit function.